Respiratory Syncytial Virus Vaccine Effectiveness in Medicare Beneficiaries Residing in Nursing Homes - Ryan E. Wiegand; Heng-Ming Sung; Yue Zhang; Andrea J. Chavez; Kelly M. Hatfield; Amber Kautz; Josephine Mak; Morgan Najdowski; Yangping Chen; Yenlin Lai; Yixin Jiao; Yoganand Chillarige; et al. (JAMA Internal Medicine, 2026)
Importance Vaccine effectiveness (VE) estimates are needed to determine the effectiveness of respiratory syncytial virus (RSV) vaccinations during their first season of availability among populations at high risk for severe RSV. Objective To assess RSV VE against RSV-associated outcomes for nursing home residents. Design, Setting, and Participants This retrospective cohort study of Medicare fee-for-service beneficiaries used electronic medical claims data from September 10, 2023, to March 30, 2024. A cohort was created for each outcome: an RSV-associated hospitalization cohort; an RSV-associated death cohort; a severe RSV-associated outcome cohort; and an RSV-associated thromboembolic event cohort. To be eligible for inclusion in a cohort, a Medicare fee-for-service beneficiary must be aged 65 years or older, reside in a US nursing home during the study period for at least 1 day, have continuous enrollment in Medicare Parts A and B (365 days prior to the index date), and have continuous enrollment in Part D (beginning on June 21, 2023). Exposure RSV vaccination. Main Outcomes and Measures Outcomes were RSV-associated hospitalization, RSV-associated death, severe RSV-associated outcomes (intensive care unit or critical care unit admission, medical ventilator use, or RSV-associated death), and RSV-associated thromboembolic event. RSV diagnoses and outcome definitions were based on claims with relevant International Classification of Diseases and Related Health Problems, Tenth Revision codes. RSV vaccine doses were determined from Medicare Part D claims using the National Drug Code Directory. Hazard ratios (HRs) from multivariable Cox proportional hazards models compared the times to first outcomes among RSV vaccinated beneficiaries and unvaccinated beneficiaries. VE was calculated as (1–HR) × 100%. Results Of 597 430 included Medicare beneficiaries (66% female; median age, 82 [IQR, 75-88] years), RSV VE against RSV-associated hospitalizations was 73% (95% CI, 65%-79%). Among beneficiaries aged 65 to 74 years VE was 60% (95% CI, 35%-76%), 75% (95% CI, 67%-82%) among beneficiaries 75 years or older, 67% (95% CI, 55%-76%) among short-stay residents (<100 cumulative days), and 80% (95% CI, 68%-87%) among long-stay residents (≥100 cumulative days). VE against RSV-associated death was 56% (95% CI, 39%-69%), VE against severe RSV-associated outcomes was 59% (95% CI, 44%-70%), and VE against RSV-associated thromboembolic events was 66% (95% CI, 44%-79%). Conclusions and Relevance In this study, in the first season of availability, RSV vaccines were associated with improved RSV-associated outcomes among US Medicare beneficiaries residing in nursing homes.